Implementing the Dubowitz assessment of gestational age in India and Malawi: a cross-sectional study of participants in a training workshop. (2021) - North, Krysten; Bellad, Roopa M.; Bose, Carl; Dhaded, Sangappa M.; Goudar, Shivaprasad S.; Herekar, Veena; Hoffman, Irving; Mvalo, Tisungane; Phiri, Melda; Saidi, Friday; Vernekar, Sunil S.; Vesel, Linda; et al.
No abstract available